Linnemannia elongata (Mortierellaceae) stimulates Arabidopsis thaliana aerial growth and responses to auxin, ethylene, and reactive oxygen species. - Natalie Vandepol; Julian Liber; Alan Yocca; Jason Matlock; Patrick Edger; Gregory Bonito (PLoS ONE, 2022)
Harnessing the plant microbiome has the potential to improve agricultural yields and protect plants against pathogens and/or abiotic stresses, while also relieving economic and environmental costs of crop production. While previous studies have gained valuable insights into the underlying genetics facilitating plant-fungal interactions, these have largely been skewed towards certain fungal clades (e.g. arbuscular mycorrhizal fungi). Several different phyla of fungi have been shown to positively impact plant growth rates, including Mortierellaceae fungi. However, the extent of the plant growth promotion (PGP) phenotype(s), their underlying mechanism(s), and the impact of bacterial endosymbionts on fungal-plant interactions remain poorly understood for Mortierellaceae. In this study, we focused on the symbiosis between soil fungus Linnemannia elongata (Mortierellaceae) and Arabidopsis thaliana (Brassicaceae), as both organisms have high-quality reference genomes and transcriptomes available, and their lifestyles and growth requirements are conducive to research conditions. Further, L. elongata can host bacterial endosymbionts related to Mollicutes and Burkholderia. The role of these endobacteria on facilitating fungal-plant associations, including potentially further promoting plant growth, remains completely unexplored. We measured Arabidopsis aerial growth at early and late life stages, seed production, and used mRNA sequencing to characterize differentially expressed plant genes in response to fungal inoculation with and without bacterial endosymbionts. We found that L. elongata improved aerial plant growth, seed mass and altered the plant transcriptome, including the upregulation of genes involved in plant hormones and "response to oxidative stress", "defense response to bacterium", and "defense response to fungus". Furthermore, the expression of genes in certain phytohormone biosynthetic pathways were found to be modified in plants treated with L. elongata. Notably, the presence of Mollicutes- or Burkholderia-related endosymbionts in Linnemannia did not impact the expression of genes in Arabidopsis or overall growth rates. Together, these results indicate that beneficial plant growth promotion and seed mass impacts of L. elongata on Arabidopsis are likely driven by plant hormone and defense transcription responses after plant-fungal contact, and that plant phenotypic and transcriptional responses are independent of whether the fungal symbiont is colonized by Mollicutes or Burkholderia-related endohyphal bacteria.